Evaluation of oxidized charcoal and urease inhibitors for increasing the efficiency of urea-based fertilizers - Guimarães, Gelton Geraldo Fernandes (2015)
Urea fertilizer can have a low agronomic efficiency when applied to the soil surface, due to N losses through NH 3 volatilization. Because of the predominance of urea in the commercial fertilizer market in recent decades, different approaches have been proposed for controlling the hydrolysis of urea and thus prolong the availability and supply of N for crop uptake. Urease inhibitors have received most of the attention, particularly N- (n-butyl) thiophosphoric triamide (NBPT) that is marketed as Agrotain ® . Alternatively, copper and zinc can be used to inhibit urease activity, which has the advantage of supplying plant-essential micronutrients. Another possibility, currently under investigation, is the use of compounds with high CEC and buffering capacity, such as oxidized charcoal, to prolong the availability of NH 4+ released in soil by urea hydrolysis. The efficiency of oxidized charcoal was assessed (OCh, 150 g kg -1 fertilizer) when applied with or without Cu and/or Zn (~ 0.5-2 g kg -1 fertilizer), relative to the use of unamended urea, for increasing N uptake by Capim-mombaça (Panicum maximum). The forage was grown in a greenhouse on a coarse-textured Oxisol, and plant material was harvested 5, 14, 28, 42 and 56 days after surface application of 15 N urea granules with or without OCh, used alone or with Cu and/or Zn, for measurement of dry matter production, total N uptake and 15 N recovery. Soil samples were also collected along with the first and fourth harvests, to determine exchangeable NH 4+ and NO 3 ‒ concentrations. Under the conditions studied, dry matter production was unaffected by the use of OCh with Cu and/or Zn; however, NH 4+ availability was prolonged by the presence of OCh. The application of Zn with urea significantly increased plant uptake of urea N and N use efficiency, presumably reflecting the antagonistic interaction of Zn with superphosphate that was applied to prevent P deficiency. A comparison was made of the effects of OCh and NBPT on the transformation of urea N in the soil. For this purpose, four soils differing in texture and CEC were incubated for 0, 1, 3, 7 and 14 days after application of pelletized 15 N urea applied with or without OCh (150 g kg -1 fertilizer) or NBPT (0.5 g kg -1 fertilizer). After each incubation period, 15 N recovery was determined as volatilized NH 3 , exchangeable NH 4+ , (NO 3 ‒ + NO 2 ‒ )-N and immobilized organic N. The OCh had little effect on any parameter measured; however, the efficacy of NBPT in retarding urea hydrolysis led to a gradual accumulation of NH 4+ that reduced NH 3 volatilization, the accumulation of NO 2 ‒ and immobilization of urea N.